The Role of Smartphone Usage in Supporting Student Participation in the Subject of Ushul Fiqih at MAN 2 Palu City - Naima, Naima; Rasak, Muh. Sarib Abdul; Nusryam, Nursyam; Indriani (DIDAKTIKA, 2025)
The advancement of increasingly sophisticated communication technology, especially in the form of Smartphones, is one of the main factors driving the increase in internet access among the public. In the world of education, education science plays a role as a link in forming a society that has individual and social foundations, as well as important elements in the implementation of education. Smartphones, with their ability to access the internet, learning applications, and interactive media, have great potential in changing learning methods and learner interactions in the classroom. This study aims to examine the role of Smartphone use in supporting students' participation in the subject of ushul fiqh at MAN 2 Palu City. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. Data analysis techniques applied include data reduction, data presentation, and verification or conclusion drawing. The results showed that the use of Smartphones at MAN 2 Palu City had a significant contribution in supporting students' participation in Ushul Fiqh subjects. The research found that there are 4 roles of Smartphone use in learning as follows: 1) Smartphones act as a substitute for projectors. 2) Smartphones act as a learning resource. 3) Smartphones can also be used as interactive learning media. 4) Smartphone acts as an exam tool The advancement of increasingly sophisticated communication technology, especially in the form of Smartphones, is one of the main factors driving the increase in internet access among the public. In the world of education, education science plays a role as a link in forming a society that has individual and social foundations, as well as important elements in the implementation of education. Smartphones, with their ability to access the internet, learning applications, and interactive media, have great potential in changing learning methods and learner interactions in the classroom. This study aims to examine the role of Smartphone use in supporting students' participation in the subject of ushul fiqh at MAN 2 Palu City. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. Data analysis techniques applied include data reduction, data presentation, and verification or conclusion drawing. The results showed that the use of Smartphones at MAN 2 Palu City had a significant contribution in supporting students' participation in Ushul Fiqh subjects. The research found that there are 4 roles of Smartphone use in learning as follows: 1) Smartphones act as a substitute for projectors. 2) Smartphones act as a learning resource. 3) Smartphones can also be used as interactive learning media. 4) Smartphone acts as an exam tool.Â Â